FREQUENCY OF DIFFICULT INTUBATION IN OBESE PATIENTS WITH NECK CIRCUMFERENCE TO THYROMENTAL DISTANCE RATIO ≥ 5.0: Difficult Intubation in Obese Patients - Qureshi, Kamil Hussain; Masood, Naveed; Malik, Usman Ejaz; Kundi, Syed Fazal-e-Karim Faisal (Pakistan Armed Forces Medical Journal, 2018)
Objective: To determine the frequency of difficult intubation in obese patients with neck circumference to thyromental distance ratio (NC/TM) ≥5.0. Study Design: Cross sectional study. Place and Duration of Study: Department of Anaesthesia, Forward Treatment Centre, Kel (Azad Kashmir) and Combined Military Hospital (CMH) Malir. Six months, from Jun 2015 to Nov 2015. Material and Methods: A total of 94 patients between the ages of 18 and 50 years with body mass index (BMI) ≥27.5 kg/m2 and NC/TM ≥5.0 who received general anesthesia requiring tracheal intubation for elective surgery (Orthopaedic, General Sugery, Urology & Gynaecology) were included in the study. Patients were induced general anaesthesia and orotracheal intubation was done by anaesthetist with at least 1 year experience. Number of intubation attempts were recorded in each patient. More than 3 attempts were considered difficult intubation. Results: Eighty two (87.2%) out of 94 obese patients with BMI ≥27.5 kg/m2 and NC/TM ≥5 had difficult intubation. Conclusion: The NC/TM ≥5 was found good predictor for difficult intubation in obese patients.